Determination Of Availability Of Cleaner Production Requirements And Mechanisms For Strengthening - Jawad Abbas, Kadhim Ahmed (Opción, 2019)
The research seeks to verify the availability of cleaner production require- ments in the General Company for Electrical and Electronic Industries, and by selecting a number of dimensions that reflect the cleaner production and according to the agreement of most writers and researchers in this subject, which are (good operational applications, replacement of raw materials, Equipment, recycling use). In order to achieve the practical aspect of the re- search and to reach the results, the inspection list was adopted as a main tool for gathering information. After the field collaboration of the researchers to the site of the research and the field on the process of production and obtain- ing the required documents as well as conducting a number of interviews with the managers concerned to find out the reality of the company investigated in terms of availability Cleaner production requirements for the purpose of completing the inspection list and answering the research questions and deter- mining the extent of ownership of the company inspected for cleaner produc- tion. The research reached a number of conclusions and recommendations. The main conclusion is that the general average level of cleaner production reached 0.84 out of 2 and 0.42 percentage points. The gap is 0.52, indicating that the level is below ambition. The most important recommendation was that the company’s management should strive to apply more practices that lead to raising the level of cleaner production.